2013
DOI: 10.1002/jsfa.6048
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pre‐slaughtering feed restriction on muscle characteristics of farmed sea bass (Dicentrarchus labrax L.) during cold storage

Abstract: Moderate feed restriction prior to slaughtering could be advisable in sea bass culture, given that no detrimental effects on fish quality or fish performance were noticed, whereas substantial amounts of feed can be saved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…In the present state of knowledge, and besides the factors mentioned above, it is safe to say that the intimate mechanisms involved in the delay of firmness loss observed remain to be ascertained. Although the physiological changes underlying the observed effects on fish fillet quality parameters are virtually unknown, it has been profusely reported that modifications in the characteristics of feeds are readily reflected in the composition of fish, especially with regard to the lipid fraction [31,71,72]. Moreover, recent studies [39] have reported that Ulva biomass at low inclusion level caused beneficial effects on the relative expression of genes involved in the lipid and protein metabolism of Solea senegalensis.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…In the present state of knowledge, and besides the factors mentioned above, it is safe to say that the intimate mechanisms involved in the delay of firmness loss observed remain to be ascertained. Although the physiological changes underlying the observed effects on fish fillet quality parameters are virtually unknown, it has been profusely reported that modifications in the characteristics of feeds are readily reflected in the composition of fish, especially with regard to the lipid fraction [31,71,72]. Moreover, recent studies [39] have reported that Ulva biomass at low inclusion level caused beneficial effects on the relative expression of genes involved in the lipid and protein metabolism of Solea senegalensis.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…Adhesiveness refers to the combination of both adhesive and cohesive force [55]. The texture of fish flesh could be influenced by a number of factors, such as the age, distribution of muscle lipids, fat content, feeding management, fish species, as well as handling stress prior slaughter [56]. In the present study, the ANOVA test indicated no noticeable difference in the adhesiveness (Figure 8(a)) and hardness (Figure 8(b)) textures of L. vannamei shrimp during iced storage (P > 0.05) even though both texture attributes revealed peak values particularly at day 11.…”
Section: Changes In Texture Attributes During Iced Storagementioning
confidence: 99%
“…After 6 days of storage, the collagen contents showed continuous decline to 4.30 mg g −1 (ice storage) and 4.46 mg g −1 (superchilling). Similar results were observed in case of sea bass fillets stored for 96 h postmortem (Saez et al ., ). Such a disintegration of collagen structure with storage time, complies well with our results, which is due to an increase in the number of detachments between muscle cells and development of cracks within muscle cells (Fig.…”
Section: Resultsmentioning
confidence: 97%